The 1560 fortifications and siege of Leith: archaeological evidence for a new transcription of the cartographic evidence. (3rd May 2016) - Paton, Kevin; Cook, Martin
Abstract : SUMMARY: Archaeological investigations at Great Junction Street, Leith, and West Bowling Green Street, Leith, revealed features that relate to the siege of Leith in 1560. Using the physical evidence from these excavations, it was possible to transcribe a map of the siege drawn at the time of the French surrender in 1560 onto a modern map of the town. This transcription and the excavation evidence, showing that the fort defences had been re-excavated on two occasions, have allowed discussions of the phasing of the fort to be put forward.